Teaching to Critical thinking in Generation Z Nursing Student: A Review of Literature - วงค์สารี, ชัชวาล (Journal of The Royal Thai Army Nurses, 2019)
This article analyses characteristics and outcomes of teaching to critical thinking for generation Z nursing student programs. Using the PICO framework to conduct a search through the Thai Journal Citation Index Centre, ScienceDirect, PubMed, and Google Scholar,the researcher obtained seven experimental studies that met the criteria. An analysis of these studies led to the following findings; 1) Critical teaching methods have 6 methods include explanation of the course clearly, self-learning, group discussion, presentation of class work with reflection techniques, cresting mild mapping for lesion, and teaching with case studies. 1.1) Time spent in the program of teaching, thinking to have effective judgment starting from 135 minutes or more depending on the lesson content. 1.2) Activities for teaching students to have critical thinking such as VARK Learning Styles, assigned to plan the concept of nursing mapping as a group, discussions and summary issues, learn teaching materials through e- learning etc., all learning activities must focus on the students to take action themselves, and t practice analyzing the simulation. 1.3) t he role of the instructor that gives the learner a critical thinking such as being a controller for the puppet to show signs according to the scenario, is the urge to thinking connection find a reason, is a reflection, and summarizing issues and guiding students to make critical decisions. and 1.4) the role of the learner must participate in the learning activities planned by the instructor and must have continuous thinking according to the program. 2) The results of the program of teaching to think critically based on empirical evidence finding; The critical thinking of students evaluated about critical thinking ability, critical thinking features, critical thinking skills, and critical problem solving ability. 2.1) the results of the thinking teaching program are critical most students after entering the program have a more critical thinking than before entering the program and in the experimental group, the critical thinking was higher than the control group. and 2.2) All program measurements are measured after the end of the trial program. There is no follow-up evaluation.